Pengelolaan Etos Kerja Guru Di Sd Negeri 04 Bejen Karanganyar - Widyaningsih, Astuti; , Prof. Dr. Sutama, M.Pd (2015)
The study aims to describe 1) Planning the work ethic of teachers in primary schools 04 Bejen Karanganyar; 2) Implementation the work ethic of teachers in Public Primary Schools 04 Bejen Karanganyar; 3) Evaluating the work ethic of teachers in Public Primary Schools 04 Bejen Karanganyar. This type of research is qualitative. The research approach uses phenomenology. Subjects were principals and teachers. Methods of data collection using in-depth interviews, observation and documentation. Data were analyzed using interactive analysis. Results of the study are: 1) Planning the work ethic of teachers in Public Primary Schools 04 Bejen Karanganyar arranged in the work plan of the school and entered the stage of collective learning activities and become a shared commitment between peer teachers and principals are supported by related parties such as superintendent of education; 2) Implementation the work ethic of teachers in Public Primary Schools 04 Bejen Karanganyar can be shown from the perspective of teachers, attitudes, as well as the spirit of teachers in understanding the real meaning of work. In practice, the teaching of which is shown from the spirit, disciplined attitude toward work time, collaboration with colleagues; 3) Evaluating the work ethic of teachers in Public Primary Schools 04 Bejen Karanganyar more revealing aspects of cooperation and supervision in a structured and continuous, which can be implemented through supervision in learning, controlling and setting work hours effectively, development potential and ability of teachers who can maximize devotion and competitions in carrying out the profession.